Why CMV is a candidate for elimination and then eradication - Paul D. Griffiths; Tabitha Mahungu (Elsevier, 2016)
Cytomegalovirus (CMV) is well-known for the end organ diseases (EODs) it causes following viraemic dissemination in immunocompromised hosts. These are termed the direct effects of CMV, where a diagnosis can be made in an individual patient. In addition, CMV is associated with indirect effects where populations can be seen to be disadvantaged compared to those without CMV. These indirect effects have been described in solid organ transplants, bone marrow transplants, advanced HIV, people admitted to intensive care units, the elderly and the general population.We summarise the evidence that associates CMV with its direct effects following congenital infection, solid organ transplantation, bone marrow transplantation and advanced HIV as well as its indirect effects in all patient populations. We propose that the greatest worldwide burden of CMV comes from its indirect effects. Control of this infection at the population level is being sought through the development of vaccines to control EODs where cost effectiveness is expected. We propose that the financial case for universal immunisation will be enhanced even further by the potential benefits vaccines may produce against the indirect effects of CMV.